COMPREENDENDO O LOCAVORISMO A PARTIR DA TEORIA DO COMPORTAMENTO PLANEJADO DECOMPOSTO (ADMPG Journal, 2023)
The objective of this article was to understand the behavioral intention and behavior of consumers in relation to Locavorism from the Theory of Decomposed Planned Behavior (TDPB). Data collection was through the application of an online questionnaire with questions from the profile of the participants and the scales referring to the TCPD constructs, and it was done by sending the link to Whatsapp groups for the purchase of local products in the city of Rio Paranaíba-MG and Viçosa-MG, on the social networks of local food producers' fairs and on the researchers' social networks. The final research sample consisted of 288 participants. To test the research hypotheses and validate the TCPD model, the Structural Equation Modeling technique was used. The results found indicate that Locavorism is influenced by consumer attitudes and, mainly, by Perceived Behavioral Control. Thus, the more positive people's attitude towards the consumption of local food and the greater the perception of access facilities and skills in using this type of food, the greater the intention to purchase and consume locally produced food.